1-(Methylaminomethyl)silatrane: Synthesis, characterization and reactivity - Sterkhova, I.V.; Lazarev, I.M.; Smirnov, V.I.; Lazareva, N.F. (Journal of organometallic chemistry, 2015)
1-(Methylaminomethyl)silatrane MeNHCH2Si(OCH2CH2)3N 2 was prepared and characterized by elemental analysis, IR, 1H, 13C, and 29Si NMR spectra. Solvate complex MeNHCH2Si(OCH2CH2)3N·C6H6 was isolated after recrystallization of silatrane 2 from benzene and its molecular structure has been determined by X-ray diffraction study. It is the first example of X-ray study of acyclic N-(silatranylmethyl)amine. The interaction silatrane 2 with HCl or CHCl3 led to the formation of its hydrochloride [MeNHCH2Si(OCH2CH2)3N]·HCl 3. The composition and structure of compound 3 was confirmed by elemental analysis, IR, 1H, 13C, 29Si NMR spectra and X-ray structure analysis. The synthesis, structure and reactivity of α-silatranylamine (1-(methylaminomethyl)silatrane) have been the subject of this investigation. [Display omitted] •1-(Methylaminomethyl)silatrane MeNHCH2Si(OCH2CH2)3N, its solvate complex and hydrochloride were synthesized.•Their structures were confirmed by IR, 1H, 13C, 29Si NMR spectrum and X-ray diffraction study.•It is first study of molecular structure of acyclic N-(silatranylmethyl)amine.